Comparison of an earth mortar and common binder mortars for indoor plastering - Lima, José (2021)
Plasters can be formulated with different binders, presenting different characteristics. Their main function is the protection of the substrate but, as indoor coatings, their influence on aesthetic performance and indoor air quality and comfort is also important. A plaster formulated with a clayish earth is compared to plasters formulated with common binders, namely hemihydrate gypsum, air lime and natural hydraulic lime. All the plasters have the same volumetric proportion binder:sand and were produced with the same siliceous washed sand. Results show that: the linear shrinkage of the earth mortar was the highest while the gypsum mortar presented no shrinkage; the bulk density of all the mortars were similar but there were differences on thermal conductivity, with advantages for the lime mortars, although this property is not significant for plasters application thicknesses; the gypsum mortar presented the highest mechanical properties while the lime mortars presented the lowest, even lower in comparison to the earth mortar; however, the resistance to dry abrasion was lower for the earth plaster; the earth plaster registers a very high hygroscopicity in comparison to all the other plasters, being an important contribution to indoor comfort, occupants health and energy consumption reduction.